Antigua and Barbuda Education Management Information System - Porta, Emilio; Klein, Jennifer; Arcia, Gustavo; Nannyonjo, Harriet (World Bank, Washington, DC, 2017)
Education data in Antigua and Barbuda is collected through both paper and electronic questionnaires. The electronic questionnaires are collected from three secondary schools through the AbusSTAR Education Management Information System (EMIS) software that was developed in Barbados. The Ministry of Education (MOE) has plans to expand the use of the EMIS software to all secondary schools, but currently continues the use of an annual paper data collection questionnaire in the absence of a fully digitized EMIS throughout the country. This report includes the following headings: facilities and equipment, EMIS staff, EMIS data, data collection, data processing, and publications.